Feeling Our Way Through the Spectrum of Videographic Criticism - Samantha Close (Akademisk Kvarter, 2024)
Critical argument can be generative in much the same way as art can be, inspiring different “correct” interpretations and new arguments. Academic filmmaking enhances this property by incorporating affective tools and texts, such as vivid footage or popular music, that move us emotionally at the same time as they form part of a critical argument—and, indeed, those emotional reactions form part of the argument. In this piece, I present a spectrum of approaches that academic filmmaking takes in the videographic criticism tradition: straightforwardly explanatory on one end and enigmatically poetic on the other. I argue that this scholarly methodology is simultaneously deeply personal and affective and, to at least the same degree, imbricated with technological infrastructures.